Characteristics physicochemical of melanin from squid ink (loligo sp.) extracted by ethanol. Issue 1 (February 2021) - Abidin, F; Sulmartiwi, L; Saputra, E
Abstract: Squid ink is liquid waste from the fishery product processing industry, it has the potential to pollute the environment because it contains a lot of organic material. Squid ink contains pigment such as melanin which is a biological material and has many benefits. Extraction using polar solvents namely Ethanol. The purpose of this study was to determine the effect of different concentrations of ethanol solvents on the extraction of melanin from squid ink (Loligo sp.) on physicochemical characteristics. The treatment used is the difference in the concentration of the solvent given, namely HCl 2 M (P0), Ethanol 2 M (P1), and Ethanol 3 M (P2) each treatment was repeated six times. The parameters of this study were protein content, fat content, and ash content), and pigment colour analysis (FT-IR) test. The results of the study showed that the difference in the concentration of the solvent used affected the yield, proximate values (protein content, fat content, and ash content), and did not eliminate the melanin content in it after the FT-IR test. The characteristics physicochemical of melanin has a different result on every parameter test. The concentration of ethanol for extracted melanin from squid ink affects the characteristics of physicochemical.